Sustain Released Bupropion in the Treatment of Tricotillomania: Outpatient Follow up Survey. (4th January 2010) - Dannon, Pinhas N.; Shoenfeld, Netta; Rosenberg, Oded; Kotler, Moshe
Abstract : Objectives . Tricotillomania (TTM) is more common than expected. SSRI's are the treatment of choice in TTM. However, response rates are lower with SSRI's. The aim of our study is to explore other pharmacological interventions. Materials and Methods . Nine female TTM patients with SSRI treatment failure were included. Sample was treated with bupropion SR up to 450 mg/day. Results . Six out of nine patients responded well to bupropion SR. Massachusetts General Hospital Hair Pulling Scale (MGH) demonstrated a significant improvement at the twelve week point (f: 32.3, power: 1, lambda: 97.1, P < .0001 ) and the response rates remained stable at sixteen-month follow up visit. Conclusions . Bupropion SR could be an alternative pharmacological treatment for TTM. Larger samples with double blind placebo controlled design are needed to confirm our preliminary report.